Revisiting board size, return on assets, and tax avoidance using Dynamic Panel Analysis: Evidence from Indonesia - Ani Siska MY; Muhammad Ramadhani (AFRE (Accounting and Financial Review), 2026)
This study investigates the influence of board size and return on assets (ROA) on tax avoidance, as well as the moderating role of board size in the relationship between ROA and tax avoidance among property and real estate companies listed on the Indonesia Stock Exchange (IDX) during 2020-2024. A quantitative approach is applied within balanced panel data, while Two-Step System Generalized Method of Moments (GMM) is utilized to address endogeneity and capture dynamic relationships among variables. The results show that board size has a positive effect on tax avoidance, indicating that larger boards tend to be associated with higher levels of tax avoidance. In contrast, ROA negatively affects tax avoidance, suggesting that more profitable firms are less likely to engage in aggressive tax planning. The findings also reveal that board size moderates the relationship between ROA and tax avoidance by weakening the negative effect of profitability in tax avoidance through enhanced monitoring and oversight functions. These results emphasize the significance of corporate governance mechanisms in influencing corporate tax behavior and provide implications for regulators and companies in promoting tax compliance while maintaining operational efficiency.